2014
DOI: 10.1111/jsm.12409
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Contraception and Female Pain, Orgasm and Sexual Pleasure

Abstract: Introduction Almost half of all pregnancies in the United States are unintentional, unplanned, or mistimed. Most unplanned pregnancies result from inconsistent, incorrect, or nonuse of a contraceptive method. Diminished sexual function and pleasure may be a barrier to using hormonal contraception. Aim This study explores sexual function and behaviors of women in relation to the use of hormonal vs. nonhormonal methods of contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 31 publications
3
41
1
8
Order By: Relevance
“…This finding differs from an adult study in which those using a hormonal contraceptive experienced less frequent sexual activity, arousal, pleasure, and orgasm 33 . It may be that our findings merely reflect the fact that, even prior to MDE onset, adolescents and young adults using hormonal contraception derive more pleasure from their sexual encounters, which prompts them to both be more sexually active and use contraception.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding differs from an adult study in which those using a hormonal contraceptive experienced less frequent sexual activity, arousal, pleasure, and orgasm 33 . It may be that our findings merely reflect the fact that, even prior to MDE onset, adolescents and young adults using hormonal contraception derive more pleasure from their sexual encounters, which prompts them to both be more sexually active and use contraception.…”
Section: Discussioncontrasting
confidence: 99%
“…Some of these limitations include combining various contraceptive methods into hormonal versus nonhormonal methods which potentially fails to capture how individual methods and hormonal components may affect a woman's sexual experiences very differently 41,63 ; exclusion of certain methods because of small numbers 64 ; small samples sizes in general 59 ; and cross-sectional study designs, which may result in bias created by not including women who had previously discontinued use of HERC. Some of these limitations include combining various contraceptive methods into hormonal versus nonhormonal methods which potentially fails to capture how individual methods and hormonal components may affect a woman's sexual experiences very differently 41,63 ; exclusion of certain methods because of small numbers 64 ; small samples sizes in general 59 ; and cross-sectional study designs, which may result in bias created by not including women who had previously discontinued use of HERC.…”
Section: Results Of Analysismentioning
confidence: 99%
“…Condoms and other barrier methods have direct effects on sensation and lubrication, whereas hormonal contraception could directly affect factors such as libido and orgasm as well. In a 2013 study comparing approximately 500 women using hormonal methods to a similarly-sized group using non-hormonal methods of contraception exclusively, researchers found that women using hormonal methods experienced lower levels of arousal, decreased sexual pleasure, fewer orgasms and more difficulties with vaginal lubrication, even when controlling for sociodemographic characteristics such as age, relationship status, sexual exclusivity status and children in the home [11]. Any method which inhibits ovulation and the mid-cycle increase in cervical fluid might impact some sexual experiences in as yet unknown ways [12].…”
Section: Ways In Which Contraception Can Affect Sexual Functioning Anmentioning
confidence: 99%